ChemInform Abstract: The Role of Copper Ions in Pathophysiology and Fluorescent Sensors for the Detection Thereof. Issue 21 (May 2015) - Verwilst, Peter; Sunwoo, Kyoung; Kim, Jong Seung
Abstract Review: [145 refs.